Strong Convergence Theorems for Common Fixed Points of an Infinite Family of Asymptotically Nonexpansive Mappings - Yuanheng Wang (Abstract and Applied Analysis)
In the framework of a real Banach space with uniformly Gateaux differentiable norm, some new viscosity iterative sequences {xn} are introduced for an infinite family of asymptotically nonexpansive mappings Tii=1∞ in this paper. Under some appropriate conditions, we prove that the iterative sequences {xn} converge strongly to a common fixed point of the mappings Tii=1∞, which is also a solution of a variational inequality. Our results extend and improve some recent results of other authors.